Recognition of a Person as an Unworthy Heir and Inheritance-Legal Sanctions upon the Mandatory Heir of the Share - Berekashvili, Diana (Journal of Law, 2019)
The civil code of Georgia imperatively defines the circle of mandatory heirs (beneficiaries), who still have the possibility to receive a certain share of inheritance against the will of the bequeather and irrespective of the contents of the will. The inheritance right constitutes the fundamental and traditional aspect of the right of private property. [1]The right of private property is the possibility to acquire property and not the property itself. [2]However, the danger exists that using this possibility will fail and the condition of the mandatory heir will essentially change contingent upon concrete legal circumstances. A human is born naturally free and this freedom is restricted with rights and obligations by a human himself, deriving from the principles of mutual respect and mutual responsibility.[3]The negligence of exactly these moral norms, which are based on mutual respect and mutual responsibility, preconditions the withholding of the rights of inheritance. The heirs whose rights of inheritance have been withheld can be divided into two groups. The first group includes those who cannot be heirs either by will or by law, i.e. unworthy heirs, and the second group includes those who cannot be heirs by law but can be heirs by a will. Such a division can be explained, on the one hand, by the necessity of prioritizing the will of a bequeather, and, on the other hand, by the necessity of considering any possible unlawful infringement of the interests of a bequeather by the heirs during his/her lifetime.[4]The presented work discusses the concept of mandatory share, the legal sanctions of withholding of inheritance and the preconditions of its implementation. [1] The Decision of the European Court of Human Rights on June 13, 1979, on the case Marckx v. Belgium, doc. № 6833/74. [2] Zoidze B., Property Law, Tbilisi, 2003, 86 (in Georgian). [3] Tchanturia L., Property of Immovables, Tbilisi, 2001, 112 (in Georgian). [4] Gongalo U. B., Legal Facts in the Inheritance Law of Russia and France, Comparative-Legal Study, Moscow, 2010, 28 (in Russian).